Single incision multiport laparoscopic appendectomy using a 2 mm alligator forceps: our experience of 60 cases - Patro, Srikant; Sahoo, Ashish K.; Muduli, Nikhil; Mishra, Ashish K.; Kumar, Tapan; Mohapatra, Kailash C. (International Surgery Journal, 2020)
Single incision laparoscopic surgery is an emerging branch of minimally assess surgery to reduce scar and post-operative pain. Appendicitis is a common general surgical problem encountered in day to day practice. Different methods of appendectomy have been described by different surgeons from open to laparoscopic and now single incision laparoscopic surgery has been practised. This is a prospective study carried out in our Department of General Surgery SCB Medical College, Cuttack from February 2019 to March 2020; 60 patients had undergone the procedure and the results are published noted under headings of post-operative pain at (6 hours, 12 hours, 24 hours and 48 hours), post-operative requirement of analgesia (diclofenac) at (6 hours, 12 hours, 24 hours and 48 hours), operative time, days to resume bowel activity, days of hospital stay, post-operative complication in accordance to Clavien-Dindo classification.